(untitled) (TEST Ticontre. Theory Text Translation, 2022)
The defeat of the Spanish Armada in the Channel in 1588 turned ‘a weak and feeble woman’ into one of the most relevant characters of late 16th-century European history: Elizabeth I, the Tudor Queen, was considered a semi-divine creature whom the myth, by comparing her to Moon goddesses like Diana and Cinthia, had made known as Semper Eadem. The identification of the queen with Cinthia became more and more evident after the events occurred in 1588, when she was hailed as the moon goddess par excellence in a series of texts written by her contemporaries. It was in that period, the last decades of the 16th century, that Sir Walter Ralegh, courtier, poet and seaman, wrote The Poems to Cynthia: a collection of short poems where Elizabeth I, the lady of the seas, is addressed as his beloved. The role of Elizabeth as Cinthia is evident above all in Ralegh’s Last Book of the Ocean to Cynthia, an unfinished poem where the author, desperate for being in disgrace, appeals to her clemency and addresses her as the empress of the ocean.